THE BALANCE CONCEPTS OF EDUCATION BASED ON ISLAM PERSPECTIVE - Abdul Wahab Syakhrani (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
This Islamic literature study tried to arrange the concept of education in Islam. To successfully compile, a series of reading reviews have been carried out starting from the formulation of the problem and continued with the collection of data from various sources related to the topic of discussion. After the collection of reading material and continued with the process of analysis in depth so that the reading material receives high understanding and interpretation. Finally, the preparation is done carefully and ensures the results of the study or findings in answering the problem of meeting the principles of validity and reliability as suggested by each scientific study. Finally the findings can be compiled, among others, that the principles and concepts of education in Islam is holding to the concept of a balance between world life and the hereafter. That is, among others, the difference between Islamic education and non-Islamic education with guidelines on the Koran and alhadis. Therefore, this Islamic study has contributed to the development of teaching and community what is a balance life in this world through researching the basic concept of life education based on Islamic perspective.